2013 IEEE International Symposium on Technology and Society (ISTAS): Social Implications of Wearable Computing and Augmediated 2013
DOI: 10.1109/istas.2013.6613118
|View full text |Cite
|
Sign up to set email alerts
|

Beyond sunglasses and spray paint: A taxonomy of surveillance countermeasures

Abstract: Abstract-The rapid decline in size and cost of networked sensors combined with increased incentives for use including monitoring physical fitness, improving public safety, increasing security, and adding convenience is causing the physical and online worlds to become heavily instrumented.Some welcome such developments, but others seek to retain privacy, often by focusing on countering the sensors themselves. Scholars have begun to consider surveillance countermeasures as a stand-alone area of research. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As we will briefly discuss later, smartphone apps with more sophisticated capabilities for rendering traffic surveillance visible en masse are also available, such as DUIBlock (2017) and Melbourne Speed Camera Alert (2017). In addition to offering an avenue for countersurveillance, these smartphone apps and Facebook pages represent surveillance countermeasures: acts undertaken with the aim of frustrating and disrupting surveillance systems (Shay et al 2013). Moreover, given the illegality of driving under the influence, crowdsourced countersurveillance can also be considered a form of what Goodman (2011) has termed 'crime-sourcing': the use of crowdsourcing techniques by distributed networks of criminals to orchestrate and undertake criminalized acts.…”
Section: Traffic Surveillance and The Rise Of Facebook Rbt Pagesmentioning
confidence: 99%
“…As we will briefly discuss later, smartphone apps with more sophisticated capabilities for rendering traffic surveillance visible en masse are also available, such as DUIBlock (2017) and Melbourne Speed Camera Alert (2017). In addition to offering an avenue for countersurveillance, these smartphone apps and Facebook pages represent surveillance countermeasures: acts undertaken with the aim of frustrating and disrupting surveillance systems (Shay et al 2013). Moreover, given the illegality of driving under the influence, crowdsourced countersurveillance can also be considered a form of what Goodman (2011) has termed 'crime-sourcing': the use of crowdsourcing techniques by distributed networks of criminals to orchestrate and undertake criminalized acts.…”
Section: Traffic Surveillance and The Rise Of Facebook Rbt Pagesmentioning
confidence: 99%
“…Research on resistance to or avoidance of surveillance has also become an area of interest within the Surveillance Studies community (Brayne 2014;Ericson 2006;Grenville 2010;Haggerty and Ericson 2006;Monahan 2006;Marx 2003;Shay et al 2013;Wilson and Serisier 2010). Gary Marx has developed, through a variety of empirical studies, a taxonomy of twelve forms of resistance or non-compliance that he refers to as "Neutralization Moves" (Marx 2009: 298; see also Marx 2003).…”
Section: Resistance and A New Political Economymentioning
confidence: 99%
“…Nonetheless, technical or policy countermeasures, such as those discussed at the 2013 IEEE International Symposium on Technology and Society [6] sometimes shift security solutions toward or into Quadrant Three. For example, consider the u.S. v. Jones decision by the u.S. Supreme Court which found that the government's use of a GPS tracking device to follow a vehicle's movements constituted a search under the Fourth Amendment.…”
Section: Quadrant Three: I Know My Rights (Accomplishes Privacy Objecmentioning
confidence: 99%